1994
DOI: 10.1016/0026-0495(94)90277-1
|View full text |Cite
|
Sign up to set email alerts
|

The effects of weight loss by exercise or by dieting on plasma high-density lipoprotein (HDL) levels in men with low, intermediate, and normal-to-high HDL at baseline

Abstract: To assess whether baseline plasma high-density lipoprotein (HDL) cholesterol levels affected the HDL response to weight loss, we examined lipoprotein changes in overweight men aged 30 to 59 years who were randomized to lose weight by exercise training (primarily running, N = 46) or by caloric restriction (ie, dieting, N = 42) or to remain sedentary, nondieting controls (N = 42) in a lyear study. In exercisers, absolute increases in HDL (mg/dL) were greatest in men with normal-tohigh baseline HDL and least in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
0
1

Year Published

1997
1997
2017
2017

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 89 publications
(40 citation statements)
references
References 25 publications
4
35
0
1
Order By: Relevance
“…A previous study showed that ten weeks of moderate-intensity exercise training significantly decreased SBP of obese children and decreased heart rate responses during exercise [20]. In this study, analysis of interaction between groups and times found that mean SBP, BMI, HC, and HDL were significantly different, consistent with studies that have shown that increased HDL levels are associated with exercise [21,22]. This study found that members of the experimental group had less sedentary time and increased HDL, whereas members of the control group had more sedentary time and decreased HDL.…”
supporting
confidence: 90%
“…A previous study showed that ten weeks of moderate-intensity exercise training significantly decreased SBP of obese children and decreased heart rate responses during exercise [20]. In this study, analysis of interaction between groups and times found that mean SBP, BMI, HC, and HDL were significantly different, consistent with studies that have shown that increased HDL levels are associated with exercise [21,22]. This study found that members of the experimental group had less sedentary time and increased HDL, whereas members of the control group had more sedentary time and decreased HDL.…”
supporting
confidence: 90%
“…The ef®cacy of exercise training in the modi®cation of blood lipids JA Halbert et al 1991; Juneau et al, 1987;King et al, 1991;Stein et al, 1990;Suter et al, 1994;Toriola, 1984;Williams et al 1994) two or more intervention groups were directly compared with one control group. In these trials, the results of the control group were over represented in the analysis.…”
Section: Discussionmentioning
confidence: 99%
“…Four trials failed to provide information on the dietary instructions or the measurement of dietary intake (Johnson et al, 1983;King et al, 1991;Suter et al, 1994;Toriola, 1984). In 19 trials, dietary intake was approximated via the completion of a 24-h (Lindheim et al, 1994), 48-h (Grandjean et al, 1996), 3-d (Baker et al, 1986;Duncan et al, 1991;Hersey et al, 1994;Houmard et al, 1994;Leon et al, 1996;Manning et al, 1991;Ready & Quinney, 1982;Ready et al, 1995;Wood et al, 1983) or 7-d (Binder et al, 1996;Hellenius 1993;Hinkleman & Nieman, 1993;Kiens et al, 1980;Nieman et al, 1993;Stensel et al, 1993;Williams et al, 1994;Wood et al, 1988) diet record at the beginning and the end of the training period. Two trials (Santiago 1995;Stein 1990) reported that dietary intake was monitored but did not report for what period.…”
Section: Quality Of Included Studiesmentioning
confidence: 99%
“…However, the increase was three-fold greater in the men who started with a baseline HDL-cholesterol greater than or equal to 48 mg/dl compared to those whose starting HDL-cholesterol was 37 mg/dl or less. 10 This paper examines the relationships of running distance to the percentile distribution of body mass index (BMI) and body circumferences (waist, hip, chest) in the National Runners' Health Study. Specifically, it tests whether crosssectional relationships of adiposity with running distance were the same at the 5th, 10th, 25th, 50th, 75th, 90th and 95th percentiles of fatness.…”
Section: Introductionmentioning
confidence: 99%